A 4-Year-Old Girl with Precocious Puberty (Journal of Enam Medical College, 2016)
Appearance of secondary sexual development before the age of nine in a male child and before the age of eight in a female child is called precocious puberty. Precocious puberty due to premature activation of the hypothalamic-pituitary axis is called central or complete precocious puberty. Incomplete precocious puberty is called if ectopic gonadotrophin secretion occurs in boys or autonomous sex steroid secretion occurs in either sex. Here we report a case of a 4-year-old girl brought to a gynecologist by her parents because of breast development, pubic hair and periodic per vaginal bleeding. Her medical history was unremarkable. The parents were of average height, and the mother reported first menstruation when she was 11 years. At physical examination, the girl was 100 cm tall, weighed 17 kg, and had a body mass index of 17. Her pubertal development is classified as Tanner stage 3 breast development and Tanner stage 2 pubic hair development.J Enam Med Col 2016; 6(3): 161-163